2018
DOI: 10.1080/09553002.2018.1484194
|View full text |Cite
|
Sign up to set email alerts
|

Low dose radiation, inflammation, cancer and chemoprevention

Abstract: Overall, LDR exerts mainly damaging effects through diverse cell and molecular mechanisms, with a few beneficial effects reported. In some cancers, surrounding adipose tissue of the breast may contribute to obesity-related cancer. Further, preclinical data suggest that anti-inflammatory dietary compounds such as PUFA and other dietary interventions may protect against radiation effects on cancer cells and cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…This is supported by the observation that mutation frequencies in cells treated with ultra-hyper-FRT doses may even be lower than in untreated cells (Redpath et al, 2003). Other recent analyses reach different conclusions (Maqsudur Rashid et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…This is supported by the observation that mutation frequencies in cells treated with ultra-hyper-FRT doses may even be lower than in untreated cells (Redpath et al, 2003). Other recent analyses reach different conclusions (Maqsudur Rashid et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, exposure of adipose-derived stem cells to LDR(1.4 Gy/min) slows the proliferation rate and causes cell cycle arrest 46 , and exposure to 10 cGy to 50 cGyLDR causes DNA damage in human adipose mesenchymal stem cell nuclei 47 or activation of the NLRP3 inflammasome inhuman lung cells 48 . In adipose cells of breast cancer tissues, LDR can activate inflammatory cytokines, the levels of which are elevated following LDR exposure 49 . Although Vibe N et al found that exposure of L6 cells to 1–2 Gy decreased insulin signalling in radiated preadipocytes 31 , there have been limited cell studies on the effects of LDR on insulin resistance in adipose cells and liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, if radiation carcinogenesis proceeds through the hosts’ recovery processes from damage in normal tissues, there could be a possibility in the future that it might be possible to develop methods to mitigate radiation-induced carcinogenesis processes. 33 Specific approaches toward this goal may include, for example, controls on the expression of cGAS, 26 GPCR (G protein-coupled receptor), 34 MK2, 35 CD28, 36 PUFA (n-3 polyunsaturated fatty acids), 37 TGFβ and PDGF 38 etc, and in turn, this may be applicable to the processes involved in spontaneous carcinogenesis. It has been reported that the use of, for example, non-steroid anti inflammatory drugs 39,40 or soy isoflavones, 41 might help prevent radiation carcinogenesis, although actual experimental data are still limited.…”
Section: Discussionmentioning
confidence: 99%